TEACHING ENGLISH PRACTICES FOR ELEMENTARY SCHOOL STUDENTS IN PACITAN - Nadilla Emma Elsadela Elsadela; Samsul Hadi; Chusna Apriyanti (The Journal Of English Teaching For Young And Adult Learners, 2026)
This study aims to describe English language teaching practices in elementary schools in Pacitan Regency, the challenges faced by teachers, and the methods applied in teaching and learning activities. This study employed a qualitative approach with a descriptive design. The research subjects consisted of four fifth-grade English teachers from four elementary schools selected using purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were subsequently analyzed using Creswell’s interactive analysis model. The findings of this study indicate that English language teaching practices across the schools share similarities and differences in the selection of materials, media used, strategies, and implementation methods, all of which are tailored to the students’ characteristics and the school environment. Teachers still face challenges related to their own competencies, students’ English proficiency, classroom management, and limited educational facilities. To overcome these obstacles, teachers employ various strategies, particularly Communicative Language Teaching (CLT), Inquiry-Based Learning, and Total Physical Response (TPR), which are integrated with a variety of learning activities. This study confirms that success in teaching English is influenced by teachers’ ability to adapt teaching strategies to students’ needs and school conditions.